Interprestasi Maulana Muhammad Ali terhadap kisah Nabi Isa a.s dalam kitab the Holy Qur'an : containing The Arabic Text With English Translation and Commentary - Roma Wijaya (Program Pascasarjana Uin Sunan Kalijaga, 2022)
et,1/ yna, c.1